Painting, photography and memory in the artistic production of Paulo Gaiad (DAPesquisa, 2021)
The text addresses the relationship established between painting and photography in the artistic production of Paulo Gaiad, seeking to analyze how the association between these different means of expression or image paradigms contributed to the constitution of this artist's poetic project, that is, a project based, according to his statements, in the phenomenon of “memory”. To this end, the study focuses on analyzing certain works by Gaiad, especially those belonging to the series As Paredes que me Cercam, A divina comédia, Memórias da cozinha e Estudos de luz e sombra. In this set of pictures, it may be suggested that the artist sought to materialize the operation of memory, seen as a process of recreating what had happened, through the juxtaposition between the pictorial and the photographic. To this end, it is worth complementing that he also used and updated traditional genres, such as landscape and still life. In this logic, the Gaiad's operating modes integrate a scenario, the contemporary art, in which the relations between the different means are of communion and not of exclusion.
Keywords: Memory in art; Gaiad, Paulo Renato, 1953-; Photography, Artistic; Still-life painting